Socioeconomic, demographic and behavioural determinants of acute respiratory infections among children under five years in Kiandutu informal settlement, Kiambu County, Kenya - W. Mburu, Nelly; Gachohi, John W.; Kiboi, Willy K. (International Journal Of Community Medicine And Public Health, 2025)
Background: Communicable diseases are a major cause of morbidity and mortality among children under five years worldwide. The global mortality associated with acute respiratory infections (ARI) among children aged below five years is 20%. ARIs are a major public health concern in both developed and developing countries. This study aimed to assess the socioeconomic, demographic and behavioral factors associated with the prevalence of ARIs among children under five years in Kiandutu Informal Settlement in Kenya. Methods: A cross-sectional analytical study was conducted which consisted of 422 child-caregiver pairs attending Kiandutu Health Centre in Kiandutu Informal Settlement, Kiambu County, Kenya. Results: The prevalence of acute respiratory infections was at 52.4% (n=221). Regression analyses revealed that socioeconomic, demographic and behavioural factors significantly associated with ARIs among children under five years were household level of income (AOR=0.41;CI: 0.24-0.70; p value <0.001 and AOR=0.10;CI: 0.02-0.50; p value=0.005), level of education (AOR=0.35; CI:0.09-1.45; p value=0.011), presence of a family member with a respiratory tract infection (AOR=2.52; CI: 1.58-4.03; p value <0.001), presence of a smoker (AOR=1.47; CI: 0.7-3.08; p value=0.003) and presence of an alcohol user (AOR=1.06; CI: 0.5-2.25; p value=0.007) in the household. Conclusions: Socioeconomic, demographic and behavioural characteristics play a critical role in influencing the occurrence of ARIs among children aged below five years.